PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Silalahi, Indah Permata Sari; Novietta, Liza; Arief, Muhammad (Journal Accounting International Mount Hope, 2025)
This study aims to determine the effect of profitability and solvency on audit delay, with company size as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sample selection method used was purposive sampling. A total of 330 observations were collected across 66 companies. The data analysis technique used in this study was moderation analysis using residual test moderation analysis with SPSS version 26. Partially, profitability and solvency had no effect on audit delay. Company size moderated the effect of profitability and solvency on audit delay.